MENINGKATKAN KETERAMPILAN MENULIS DESKRIPSI DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA SISWA KELAS IV SEKOLAH DASAR - Ramadani, Silvi; Viora, Dwi; Syahrul Rizal, Muhammad; Lesmana Alim, Melvi; Asilestari, Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The study is intended to improve writing skills on the fourth grade of primary school (SDN) 007 bangkinang, using contextual teaching and learning (CTL) approaches. This type of research is a collaborative class action study. Research design using the models of kemmis and robin McTaggart that include: planning, action, observation, and reflection. The study is carried out in two cycles. The subject of this study is the fourth graders of 007 bangkinang who numbered 22 students. The instruments used were the test of writing and observation ability. The technical data analysis is the quantitative descriptive analysis technique. The results of the study on the improvement of the decomposition skills using a CTL approach in the fourth grade of 007 should be a 2024/2025 state student before applying the 20/2025 rating of the student's starting point of view before applying the CTL rating of the value of writing an essay of 65.66, on the I cycle increasing to 69.04 and on cycle ii increasing to 75.40. CTL approach application measures to the study are: 1) constructing a student's knowledge with a q and a, 2) conducting an incubation activity by making direct observations of the school environment, 3) developing a student's curiosity by asking, 4) creating a learning community by forming a study group, 5) presenting a model as a learning group, and 6) Conduct an assessment of the student writing results.